SISTEM PENDUKUNG KEPUTUSAN UNTUK MENENTUKAN KELAYAKAN SERTIFIKASI GURU DENGAN MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING (STUDI KASUS : SMPN 42 MEDAN) - BASTANTA, CHRIS DIAN (Majalah Ilmiah Kaputama, 2019)
In carrying out a quality education process is an obligation and a requirement that is demanded for every school, as well as the 42 Medan SMP has a certified teacher. Providing certification to teachers needs to be reviewed because many teachers are not yet entitled to receive certification but have received certification. Therefore the solution is made a Decision Support System using the Simple Additive Weighting method to assist schools in determining teachers who are eligible to receive certification with criteria that are pedagogical, personality, social, professional. The application was built using the Microsoft Visual Studio 2010 programming language and as the MySQL database. The results of the study were an application of a teacher certification eligibility decision-making system that was able to be used by school principals in determining the eligibility of teacher certification at 42 SMP Medan.